Common Geometry Shapes Formas Geometricas: An Introductory-English Lesson & Introductory Spanish Lesson - Jaramillo, James A.; Solano, Angele ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1946)
A lesson plan for first-grade children beginning to learn English describes an activity using manipulatives and visual aids to develop recognition of three geometric shapes (circle, square, rectangle), their names, and a few additional words in English (e.g., "bag,""table,""door"). Students are grouped at tables of four to six and provided with name-marked items of the appropriate shape. When directed by the teacher, students match the shape indicated with the corresponding item on the table, then practice pronunciation of the English word. Subsequently, students are instructed to bring the items to a central location, and are encouraged to find other similar shapes within the classroom. (MSE)
Teachers.
Practitioners.
Microfiche.
Keywords: Bilingual Education; Class Activities; Classroom Techniques; English (Second Language); Geometric Concepts; Geometry; Grade 1.; Introductory Courses; Lesson Plans; Manipulative Materials; Mathematics Instruction; Primary Education; Spanish Speaking; Visual Aids; Guides, Classroom -- Teacher